China-Pakistan Relations in 2021 and China's Image in Pakistan's Mainstream English Newspapers - Jin, Qiang; Hou , Minghan (Pacific International Journal, 2023)
This paper adopts a combination of qualitative and quantitative analysis to describe the basic trend of China-Pakistan relations and the main achievements of China-Pakistan cooperation in 2021, and also summarizes the basic characteristics of China's studies on Pakistan. This paper also focuses on exploring China's national image in Pakistani media in 2021. It is found that in the mainstream media of Pakistan, the major country diplomacy, China's economic development and China's politics with China-Pakistan relations as the core are rich in content, prominent in image and a large proportion of positive reports. The positive attitude of the articles in the mainstream media in Pakistan, written by elites from all levels in both China and Pakistan, deeply reflects the recognition of China's achievements in recent years and the expectation of a bright future of cooperation between China and Pakistan under the framework of the China-Pakistan Economic Corridor.